Primary tubercular otitis media: a rare case report - Sharma, Vishal; Bhagat, Sanjeev; Sahni, Dimple; Sharma, Dinesh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Tubercular otitis media is a rare presentation of tuberculosis. High index of suspicion is required for diagnosis. We present a rare case of tubercular otitis media presenting as post auricular swelling with no evidence of pulmonary or any other foci of tuberculosis. Diagnosis was made on the basis of acid fast bacilli seen in fine needle aspirate. Anti-tubercular drugs were initiated and patient responded well to treatment.